Sodium-free negative electrode sodium battery and application thereof

By using magnesium foil current collector as the negative electrode sheet in a sodium-free negative electrode battery, the problems of poor circulation stability, low capacity and high production cost are solved, and a battery with high energy density and long cycle stability is achieved.

CN119419336APending Publication Date: 2025-02-11QINGDAO INST OF BIOENERGY & BIOPROCESS TECH CHINESE ACADEMY OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411576039.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

Existing sodium-free anode sodium batteries have poor circulation stability, low capacity and high production cost.

Method used

Magnesium foil current collector is used as the negative electrode sheet to replace the traditional copper foil or aluminum foil current collector, and achieve stable and efficient sodium metal deposition and peeling without interface modification or surface coating.

Benefits of technology

The capacity retention rate during battery cycle has been greatly improved, the energy density has reached ≥300Wh/kg, and the capacity retention rate of 500 cycles is greater than 80%, reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119419336A_ABST
    Figure CN119419336A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of batteries, and particularly relates to a sodium battery with a sodium-free negative electrode and application of the sodium battery. The sodium battery with the sodium-free negative electrode takes a magnesium foil current collector as a negative electrode plate. The sodium battery with the sodium negative electrode has the beneficial effects that the magnesium foil current collector is adopted as the negative electrode piece, traditional current collectors such as copper foil and aluminum foil are replaced, and stable and high-efficiency sodium metal deposition and stripping can still be realized under the condition that interface modification or surface coating is not required to be performed on the negative electrode piece; the capacity retention rate in the battery circulation process is greatly improved; the energy density of the sodium battery with the sodium-free negative electrode is greater than or equal to 300Wh / kg, and the sodium battery has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries, and in particular relates to a sodium-free negative electrode sodium battery and applications thereof. Background Art

[0002] With the gradual upgrading of social energy structure, the rapid development of renewable energy generation and smart grid, the requirements for high safety, high energy density, high power density, low cost and other characteristics of battery energy storage systems are constantly increasing. Lithium-ion batteries, which currently dominate the fields of portable electronic devices and new energy vehicles, are limited by the risk of lithium resource shortage and its unbalanced distribution around the world. Based on the above problems, finding a suitable alternative battery system has become the focus of current researchers in electrochemical energy storage technology.

[0003] Sodium-ion batteries have become one of the most attractive electrochemical energy storage materials in the "post-lithium era" due to their abundant resources, good economy and environmental sustainability. However, limited by the relatively large ion size and weight of sodium ions, the energy density of current sodium-ion batteries is generally lower than that of commercial lithium-ion batteries. Although sodium-ion batteries are considered to be a promising candidate for lithium-ion batteries, if the energy density and cost issues of sodium-ion batteries are not well solved, it will be difficult to develop practical applications even in the field of large-scale energy storage. The battery design without sodium negative electrode is expected to significantly improve the energy density of sodium batteries because there is no negative electrode active material, and it is possible to match or even surpass traditional lithium-ion batteries in terms of energy density and cost.

[0004] Since the sodium ions of sodium-free negative electrode sodium batteries are only provided by the active materials in the positive electrode, the uneven deposition morphology will lead to the generation of "dead sodium" during the repeated deposition and stripping of sodium metal on the negative electrode side, resulting in reduced coulombic efficiency. Existing sodium-free negative electrode sodium batteries mainly improve the deposition process of sodium metal by modifying the negative electrode interface and regulating the interface between the negative electrode and the electrolyte, or use sodium supplements to offset the loss of sodium ions during the deposition / stripping process, but these modification methods generally have more complicated processing techniques, which are not conducive to actual large-scale production. Summary of the invention

[0005] The present application provides a negative electrode-free sodium battery and its application, aiming to solve the problems of poor cycle stability, low capacity, and high production cost of existing negative electrode-free sodium batteries.

[0006] In a first aspect, the present application provides a sodium-free negative electrode sodium battery, wherein the sodium-free negative electrode sodium battery uses a magnesium foil current collector as a negative electrode plate, and the thickness of the magnesium foil current collector is 10-50 um.

[0007] The sodium negative electrode sodium battery described in the present application adopts a magnesium foil current collector as the negative electrode plate, replacing traditional current collectors such as copper foil and aluminum foil. It can still achieve stable and efficient sodium metal deposition and stripping without the need for interface modification or surface coating of the negative electrode plate, greatly improving the capacity retention rate during the battery cycle; the energy density of the sodium-free negative electrode sodium battery described in the present application is ≥300Wh / kg, and has broad application prospects.

[0008] According to some embodiments of the sodium-free negative electrode sodium battery described in the present application, the thickness of the magnesium foil current collector is 20-30 um.

[0009] According to some embodiments of a sodium-free negative electrode sodium battery described in the present application, the sodium-free negative electrode sodium battery also includes a positive electrode plate, a separator and a boron-based electrolyte.

[0010] According to some embodiments of a sodium-free negative electrode sodium battery described in the present application, the boron-based electrolyte includes a boron-containing sodium salt and an ether solvent.

[0011] According to some embodiments of the sodium-free negative electrode sodium battery described in the present application, the boron-containing sodium salt includes one or more of sodium tetrafluoroborate, sodium tetrakis(hexafluoroisopropyl)borate and perfluoroalcohol sodium borate;

[0012] The structural formula of the sodium perfluoroborate is as follows:

[0013]

[0014] According to some embodiments of a sodium-free negative electrode sodium battery described in the present application, the ether solvent includes one or more of tetrahydrofuran, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether and tetraethylene glycol dimethyl ether.

[0015] According to some embodiments of a sodium-free negative electrode sodium battery described in the present application, the concentration of the boron sodium salt in the boron-based electrolyte is 0.1-2M.

[0016] According to some embodiments of a sodium-free negative electrode sodium battery described in the present application, the concentration of the boron sodium salt in the boron-based electrolyte is 0.6-1.0M.

[0017] According to some embodiments of the sodium-free negative electrode sodium battery described in the present application, the positive electrode plate includes a positive electrode active material, a conductive agent and a binder.

[0018] According to some embodiments of a sodium-free negative electrode sodium battery described in the present application, the positive electrode active material includes one or more of Na3V2(PO4)2F3, Na3V2(PO4)3 and transition metal layered oxides.

[0019] According to some embodiments of the sodium-free negative electrode sodium battery described in the present application, the transition metal layered oxide includes NaMnO2, Na 0.9 [Cu 0.22 Fe 0.30 Mn 0.48 ]O2、Na 0.9 [Cu 0.22 Fe 0.30 Mn 0.48 ]O2、Na 0.66 Ni 0.17 Co 0.17 Ti 0.66 One or more of O2.

[0020] According to some embodiments of the sodium-free negative electrode sodium battery described in the present application, the conductive agent includes one or more of graphene, acetylene black, graphite, carbon nanotubes, conductive carbon black, vapor-grown carbon fiber and Ketjen black.

[0021] According to some embodiments of the sodium-free negative electrode sodium battery described in the present application, the binder includes one or more of polyvinylidene fluoride, polyacrylic acid, sodium hydroxymethyl cellulose, polytetrafluoroethylene and polyvinyl alcohol.

[0022] According to some embodiments of a sodium-free negative electrode sodium battery described in the present application, the mass ratio of the positive electrode active material, the conductive agent and the binder in the positive electrode plate is: (80-95): (2-15): (5-10).

[0023] According to some embodiments of the sodium-free negative electrode sodium battery described in the present application, the thickness of the positive electrode plate is 100um-1000um.

[0024] According to some embodiments of the sodium-free negative electrode sodium battery described in the present application, the separator includes one or more of a polyethylene separator, a polypropylene separator, a cellulose separator and a glass fiber separator.

[0025] The electrical device described in the present application has the characteristics of high specific capacity and long service life.

[0026] According to some embodiments of the sodium-free negative electrode sodium battery described in the present application, the thickness of the separator is 8um-800um.

[0027] In a second aspect of the present application, an electrical device is provided, comprising the sodium-free negative electrode sodium battery described in the first aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a schematic diagram of the operation of the sodium-free negative electrode sodium battery described in Example 1 of the present application;

[0029] Figure 2This is a SEM image of sodium deposited on the magnesium foil negative electrode described in Example 1 of the present application;

[0030] Figure 3 This is a SEM image of sodium deposited on a copper foil current collector as described in Comparative Example 1 of the present application;

[0031] Figure 4 This is a charge and discharge curve diagram of the sodium-free negative electrode sodium battery described in Example 1 of the present application at a current density of 100 mA / g;

[0032] Figure 5 This is a long cycle performance diagram of the negative electrode-free sodium battery described in Example 1 of the present application at a current density of 100 mA / g;

[0033] Figure 6 This is a charge and discharge curve diagram of the sodium-free negative electrode sodium battery described in Example 4 of the present application at a current density of 100 mA / g;

[0034] Figure 7 This is a charge and discharge curve of the sodium-free negative electrode sodium battery described in Comparative Example 1 of the present application at a current density of 100 mA / g;

[0035] Figure 8 This is a charge and discharge curve diagram of the sodium-free negative electrode sodium battery described in Comparative Example 3 of the present application at a current density of 100 mA / g. DETAILED DESCRIPTION

[0036] Embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.

[0037] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0038] An embodiment of the present application provides a sodium-free negative electrode sodium battery, wherein the sodium-free negative electrode sodium battery uses a magnesium foil current collector as a negative electrode plate, and the thickness of the magnesium foil current collector is 10-50um, for example, 10um, 15um, 20um, 23um, 28um, 32um, 37um, 40um, 46um, 50um, etc.

[0039] The sodium negative electrode sodium battery described in the present application adopts a magnesium foil current collector as the negative electrode plate, replacing traditional current collectors such as copper foil and aluminum foil. Stable and efficient sodium metal deposition and stripping can be achieved without interface modification or surface coating of the negative electrode plate, which greatly improves the capacity retention rate during the battery cycle. The energy density of the sodium-free negative electrode sodium battery described in the present application is ≥300Wh / kg, and the capacity retention rate of the battery after 500 cycles is greater than 80%, which has broad application prospects.

[0040] The sodium-free negative electrode sodium battery described in the present application uses a magnesium foil current collector as the negative electrode plate, which reduces the volume and mass proportion of the negative electrode in the battery. Since the magnesium foil surface has a strong adsorption force for sodium ions, it can provide a large number of evenly distributed sodium metal nucleation sites to induce uniform deposition of sodium metal. That is, a strong and uniform SEI layer is formed on the surface of the magnesium foil current collector, inducing flat, uniform and dendrite-free growth of sodium metal on the surface of the magnesium foil current collector.

[0041] Batteries that use magnesium foil current collectors as negative electrode sheets form hybrid batteries containing sodium ions and magnesium ions in situ in the electrolyte. The addition of magnesium ions promotes the reversible deposition and stripping of sodium metal on the negative electrode side and the reversible deintercalation of sodium ions on the positive electrode side, minimizing the generation of "dead sodium" and greatly improving the capacity retention rate during the battery cycle, thereby obtaining a sodium-free negative electrode sodium battery with high energy density and long cycle stability.

[0042] In some embodiments of the present application, the thickness of the magnesium foil current collector is 20-30um. The thinner the thickness of the magnesium foil current collector, the higher the energy density of the assembled negative electrode-free sodium battery. However, the preparation process of thinner magnesium foil is relatively complicated, and foil with a thickness of 20um-30um can be easily achieved in current rolling technology.

[0043] In some embodiments of the present application, the sodium-free negative electrode sodium battery also includes a positive electrode plate, a separator and a boron-based electrolyte.

[0044] In some embodiments of the present application, the boron-based electrolyte includes a boron-containing sodium salt and an ether solvent. Since the ether solvent has good deposition and stripping efficiency, the electrolyte formed by the boron-containing sodium salt and the ether solvent has good interface compatibility with the magnesium foil, which is beneficial to reduce the loss of active sodium ions in the cycle, and realizes the high reversibility of the sodium-free negative electrode sodium battery cycle.

[0045] In some embodiments of the present application, the boron-containing sodium salt includes one or more of sodium tetrafluoroborate, sodium tetrakis(hexafluoroisopropyl)borate and sodium perfluoroborate. The present application selects a boron-containing sodium salt electrolyte with high oxidation stability, which can match high-voltage positive electrode materials. The inorganic fluoride formed on the negative electrode side is conducive to the flat, dendrite-free planar growth of sodium metal on the negative electrode current collector, reducing the side reaction between the high-voltage positive electrode and the ether-based electrolyte, and helping to improve the high-voltage stability of the electrolyte.

[0046] The structural formula of the sodium perfluoroborate is as follows:

[0047]

[0048] The reference website for the preparation method of sodium perfluoroborate described in the examples of this application is: https: / / onlinelibrary.wiley.com / doi / 10.1002 / anie.202202133.

[0049] In some embodiments of the present application, the ether solvent includes one or more of tetrahydrofuran, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether and tetraethylene glycol dimethyl ether.

[0050] In some embodiments of the present application, the concentration of the sodium borate in the boron-based electrolyte is 0.1-2 M, such as 0.1 M, 0.5 M, 0.8 M, 1.0 M, 1.2 M, 1.6 M, 2 M, etc. Within this concentration range, the electrolyte has an appropriate sodium ion concentration, which is conducive to achieving a high coulombic efficiency of sodium deposition / stripping.

[0051] In some embodiments of the present application, the concentration of sodium borate in the boron-based electrolyte is 0.6-1.0M.

[0052] In some embodiments of the present application, the positive electrode sheet includes a positive electrode active material, a conductive agent and a binder.

[0053] In some embodiments of the present application, the positive electrode active material includes one or more of Na3V2(PO4)2F3, Na3V2(PO4)3 and transition metal layered oxides.

[0054] In some embodiments of the present application, the transition metal layered oxide includes NaMnO2, Na 0.9 [Cu 0.22 Fe 0.30 Mn 0.48 ]O2、Na 0.9 [Cu 0.22 Fe 0.30 Mn 0.48 ]O2、Na 0.66 Ni0.17 Co 0.17 Ti 0.66 One or more of O2.

[0055] In some embodiments of the present application, the conductive agent includes one or more of graphene, acetylene black, graphite, carbon nanotubes, conductive carbon black, vapor-grown carbon fiber and Ketjen black.

[0056] In some embodiments of the present application, the binder includes one or more of polyvinylidene fluoride (PVDF), polyacrylic acid (PAA), sodium carboxymethyl cellulose (CMC), polytetrafluoroethylene (PTFE) and polyvinyl alcohol (PVA).

[0057] In some embodiments of the present application, the mass ratio of the positive electrode active material, the conductive agent and the binder in the positive electrode plate is: (80-95): (2-15): (5-10).

[0058] In some embodiments of the present application, the thickness of the positive electrode plate is 100um-1000um, for example, 100um, 200um, 280um, 320um, 430um, 500um, 560um, 630um, 680um, 730um, 790um, 810um, 860um, 940um, 1000um, etc.

[0059] In some embodiments of the present application, the method for preparing the positive electrode plate includes the following steps: mixing and grinding the positive electrode active material, the conductive agent and the binder, and diluting with an organic solvent to obtain a slurry, and evenly coating the obtained slurry on an aluminum foil current collector and drying it.

[0060] In some embodiments of the present application, the positive electrode sheet is obtained by tape casting. The positive electrode active material, the conductive agent and the binder in a mass ratio of 80:10:10 are dissolved in a solvent to obtain a slurry, and the slurry is coated on an aluminum foil using a four-sided wet film preparation device. The thickness of the coating formed on the aluminum foil can be 50-500um.

[0061] In some embodiments of the present application, the ratio of the mass of the solvent to the total mass of the positive electrode active material, the conductive agent and the binder is (1-3):1, for example, 1:1, 1.5:1, 2:1, 3:1, etc.

[0062] In some embodiments of the present application, the solvent includes one or more of water, N-methylpyrrolidone and ethanol.

[0063] In some embodiments of the present application, the separator includes one or more of a polyethylene separator, a polypropylene separator, a cellulose separator and a glass fiber separator.

[0064] In some embodiments of the present application, the thickness of the diaphragm is 8um-800um, for example, 8um, 20um, 50um, 100um, 120um, 230um, 340um, 450um, 560um, 680um, 720um, 800um, etc.

[0065] The present application also provides an electrical device, comprising the sodium-free negative electrode sodium battery described in the first aspect of the present application.

[0066] The electrical device described in the present application has the characteristics of high specific capacity and long service life.

[0067] The technical solution of the present application is described in detail below in conjunction with specific embodiments.

[0068] Example 1

[0069] A sodium-free negative electrode sodium battery comprises a magnesium foil current collector negative electrode sheet, a positive electrode sheet, a separator and a boron-based electrolyte.

[0070] The method for preparing the sodium-free negative electrode sodium battery comprises the following steps:

[0071] (1) Preparation of positive electrode sheet:

[0072] The positive electrode active material Na3V2(PO4)2F3, the conductive agent Ketjen black, and the binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 8:1:1, and the mixture is added into N-methylpyrrolidone (NMP) to form a slurry, wherein the mass ratio of the total mass of the positive electrode active material, the conductive agent and the binder to the N-methylpyrrolidone is 1:5;

[0073] The slurry was evenly coated on aluminum foil using a 125 μm thick four-sided wet film preparation device and dried in a 110°C vacuum oven for two hours, then transferred to an 80°C oven and dried overnight to obtain a positive electrode sheet with a thickness of 125 μm.

[0074] (2) Preparation of electrolyte:

[0075] In an argon atmosphere glove box, 0.01 mol sodium borohydride (NaBH4) and 0.04 mol hexafluoroisopropanol (C3H2F6O) were dissolved in 15 ml ethylene glycol dimethyl ether solvent and fully reacted for 6 hours. The ethylene glycol dimethyl ether solvent was removed by vacuum evaporation to generate 0.01 M sodium tetrakis(hexafluoroisopropyl)borate (NaB(hfip)4).

[0076] The above 0.001M sodium tetrakis(hexafluoroisopropyl)borate (NaB(hfip)4) was weighed and dissolved in 1 ml of diethylene glycol dimethyl ether solvent, and fully dissolved under magnetic stirring until clear to obtain an electrolyte with a concentration of 1 mol / L.

[0077] (3) Assembling sodium batteries

[0078] like Figure 1 As shown, the button cell is assembled in the order of the negative electrode shell, magnesium foil current collector, electrolyte, separator, positive electrode sheet and positive electrode shell.

[0079] The separator used is a glass fiber (Whatman, GF / D) separator with a thickness of 675 um, the electrolyte is a diethylene glycol dimethyl ether solution of sodium tetrakis(hexafluoroisopropyl)borate (NaB(hfip)4) (sodium salt concentration is 1 mol / L), and the thickness of the magnesium foil current collector is 20 um.

[0080] Example 2

[0081] The difference between the sodium-free negative electrode sodium battery in Example 2 and Example 1 is that the thickness of the magnesium foil current collector in Example 2 is 50 μm. The other steps are the same as in Example 1.

[0082] Example 3

[0083] The sodium-free negative electrode sodium battery described in Example 3 is different from that in Example 1 only in that the positive electrode active material used in Example 3 is sodium alum phosphate positive electrode, and the other steps are the same as in Example 1.

[0084] Example 4

[0085] The difference between the sodium-free negative electrode sodium battery in Example 4 and Example 1 is that the positive electrode active material used in Example 4 is Na 0.9 [Cu 0.22 Fe 0.30 Mn 0.48 ]O2.

[0086] Example 5

[0087] The sodium-free negative electrode sodium battery described in Example 5 is different from that in Example 1 only in that sodium tetrafluoroborate is used instead of sodium tetrakis(hexafluoroisopropyl)borate (NaB(hfip)4) during the preparation process of the sodium-free negative electrode sodium battery described in Example 5.

[0088] Example 6

[0089] The sodium-free negative electrode sodium battery described in Example 6 is different from that in Example 1 only in that: the sodium-free negative electrode sodium battery described in Example 6 uses sodium perfluoroborate instead of sodium tetrakis(hexafluoroisopropyl)borate (NaB(hfip)4) during the preparation process.

[0090] Comparative Example 1

[0091] The sodium-free negative electrode sodium battery described in Comparative Example 1 is different from that in Example 1 only in that: the sodium-free negative electrode sodium battery described in Comparative Example 1 uses a copper foil current collector instead of a magnesium foil current collector during the preparation process.

[0092] Comparative Example 2

[0093] The sodium-free negative electrode sodium battery described in Comparative Example 2 is different from that in Example 1 only in that: in the preparation process of the sodium-free negative electrode sodium battery described in Comparative Example 2, a carbon-coated aluminum foil is used to replace the magnesium foil current collector.

[0094] Comparative Example 3

[0095] The sodium-free negative electrode sodium battery described in Comparative Example 3 is different from that in Example 1 only in that the sodium-free negative electrode sodium battery described in Comparative Example 3 uses NaPF6 instead of sodium tetrakis(hexafluoroisopropyl)borate (NaB(hfip)4) during the preparation process.

[0096] Performance study of the sodium-free negative electrode sodium battery described in Examples 1-6 of the present application and the sodium-free negative electrode sodium battery described in Comparative Examples 1-3:

[0097] The sodium-free negative electrode sodium batteries of Examples 1-6 and Comparative Examples 1-3 of the present application were subjected to charge and discharge cycle tests at a current density of 100 mA / g, and the charge and discharge capacity, first cycle discharge specific capacity, discharge specific capacity when the battery was cycled for 100 cycles, 100 cycle coulomb efficiency and 100 cycle capacity retention rate of each battery were recorded. The results are shown in Table 1:

[0098] Table 1

[0099]

[0100] It can be seen from Table 1 that the sodium-free negative electrode sodium battery described in the present application has higher charge and discharge coulomb efficiency and long cycle capacity retention rate than the sodium battery described in Comparative Examples 1-3. The sodium-free negative electrode sodium battery prepared in Comparative Examples 1-3 cannot reach 100 cycles due to poor battery cycle stability.

[0101] Under the current density test of 100 mA / g, the SEM images of the magnesium foil current collector of the battery in Example 1 and the copper foil current collector of the battery in Comparative Example 1 are as follows: Figure 2 and Figure 3 As shown:

[0102] from Figure 2 and Figure 3 It can be seen that the uniform and flat deposition and growth of sodium metal on the magnesium foil current collector of the battery described in the present application effectively alleviates the formation of sodium dendrites, reduces the generation of dead sodium, and is beneficial to improving the cycle stability of the battery. This is due to the fact that the magnesium foil current collector provides more nucleation sites for sodium metal deposition; while many sodium dendrites are formed on the copper foil current collector of the battery described in Comparative Example 1.

[0103] Under the current density test of 100 mA / g, the charge and discharge capacities of the sodium-free negative electrode sodium batteries described in Example 1, Example 4, Comparative Example 1 and Comparative Example 3 and the cycle performance of the sodium-free negative electrode sodium battery described in Example 1 are respectively as follows: Figure 4 , Figure 6 , Figure 7 , Figure 8 and Figure 5 As shown;

[0104] from Figure 4-Figure 8 It can be seen that the sodium-free negative electrode sodium battery described in the present application has a higher charge and discharge capacity than the sodium-free negative electrode sodium battery described in Comparative Examples 1 and 3. This is due to the fact that the negative electrode magnesium foil and the boron-containing sodium salt electrolyte of the sodium-free negative electrode sodium battery described in the present application form a strong and uniform SEI layer in situ during the battery cycle, inducing the flat and uniform dendrite-free growth of sodium metal on the negative electrode surface of the magnesium foil, greatly improving the battery cycle stability.

[0105] Although the above embodiments have been shown and described, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. Changes, modifications, substitutions and variations of the above embodiments by those of ordinary skill in the art are all within the scope of protection of the present invention.

Claims

1. A sodium-free negative electrode sodium battery, characterized in that: The sodium-free negative electrode sodium battery uses a magnesium foil current collector as the negative electrode plate; the thickness of the magnesium foil current collector is 10-50 um.

2. The sodium-free negative electrode sodium battery according to claim 1, characterized in that: The thickness of the magnesium foil current collector is 20-30 um.

3. The sodium-free negative electrode sodium battery according to claim 1, characterized in that: The sodium-free negative electrode sodium battery also includes a positive electrode plate, a separator and a boron-based electrolyte.

4. The sodium-free negative electrode sodium battery according to claim 3, characterized in that: The boron-based electrolyte comprises a boron-containing sodium salt and an ether solvent.

5. The sodium-free negative electrode sodium battery according to claim 4, characterized in that: The boron-containing sodium salt includes one or more of sodium tetrafluoroborate, sodium tetrakis(hexafluoroisopropyl)borate and sodium perfluoroborate; The structural formula of the sodium perfluoroborate is as follows:

6. The sodium-free negative electrode sodium battery according to claim 4, characterized in that: The ether solvent includes one or more of tetrahydrofuran, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether and tetraethylene glycol dimethyl ether.

7. The sodium-free negative electrode sodium battery according to claim 4, characterized in that: The concentration of boron sodium salt in the boron-based electrolyte is 0.1-2M, preferably 0.6-1.0M.

8. The sodium-free negative electrode sodium battery according to any one of claims 3 to 7, characterized in that: The positive electrode sheet comprises a positive electrode active material, a conductive agent and a binder; Preferably, the positive electrode active material includes one or more of Na3V2(PO4)2F3, Na3V2(PO4)3 and transition metal layered oxides; more preferably, the transition metal layered oxides include NaMnO2, Na 0.9 [Cu 0.22 Fe 0.30 Mn 0.48 ]O2、Na 0.9 [Cu 0.22 Fe 0.30 Mn 0.48 ]O2、Na 0.66 Ni 0.17 Co 0.17 Ti 0.66 One or more of O2; Preferably, the conductive agent includes one or more of graphene, acetylene black, graphite, carbon nanotubes, conductive carbon black, vapor-grown carbon fiber and Ketjen black; Preferably, the binder comprises one or more of polyvinylidene fluoride, polyacrylic acid, sodium hydroxymethyl cellulose, polytetrafluoroethylene and polyvinyl alcohol; Preferably, the mass ratio of the positive electrode active material, the conductive agent and the binder in the positive electrode sheet is: (80-95): (2-15): (5-10); Preferably, the thickness of the positive electrode plate is 100um-1000um.

9. The sodium-free negative electrode sodium battery according to any one of claims 3 to 7, characterized in that: The separator includes one or more of a polyethylene separator, a polypropylene separator, a cellulose separator and a glass fiber separator; Preferably, the thickness of the diaphragm is 8um-800um.

10. An electrical device, characterized in that: A sodium-free negative electrode sodium battery comprising the sodium-free negative electrode described in any one of claims 1 to 9.